Effects of Aluminum Substitution Configurations on the Catalytic Performance of Iron-Substituted Zeolite MFI for N2O Activation - MONTEJO-VALENCIA, BRIAN D. (LACCEI, 2024)
This study investigates the catalytic performance ofiron-substituted zeolite MFI for N2O activation, focusing on theimpact of aluminum substitution configurations on the catalyticperformance of the zeolite. Our results indicate that the preferablesite for the substitution of aluminum is in the T11-T2 position, withthe strongest adsorption observed in the T11-T1 position.Furthermore, the most favorable activation of N2O was found tooccur in the T7-T1 position. These findings provide crucial insightsinto the role of aluminum substitution in the design of highperformancezeolite catalysts for N2O activation. Overall, this studycontributes to the advancement of efficient and sustainable strategiesfor the removal of N2O from industrial processes.